Inventory Visibility and Performance of Large Food and Beverage Manufacturing Firms in Kenya - Mose, Douglas Isaaka; Osoro, Anthony; Nyang’au, Samson (Journal Integration of Management Studies, 2024)
This study aimed to examine the impact of inventory visibility on the performance of large food and beverage manufacturing firms in Kenya. The research grounded the network perspective theory and employed a cross-sectional design. The target population comprised 561 individuals from 187 large-scale food and beverage manufacturing firms in Kenya, with human resource managers as the primary respondents, given their role as custodians of employee records. Using stratified random sampling, a sample of 228 respondents was selected. Data was collected through a structured questionnaire and pilot-tested on 10% of the sample to verify its validity and reliability before full deployment. Data analysis involved both descriptive and inferential statistical methods. The findings indicated that inventory visibility had not been effectively integrated into most firms surveyed. Furthermore, a strong and significant correlation was identified between inventory visibility and the performance of food and beverage manufacturing firms in Kenya. The study concluded that the lack of effective integration of inventory visibility contributed to inefficient inventory management, adversely affecting organizational performance. Accordingly, it is recommended that manufacturing firms enhance their supply chain processes by improving inventory visibility, allowing for more effective tracking of inventory flows to support improved performance outcomes.